2007
DOI: 10.1038/sj.jcbfm.9600500
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Brain Inflammation with [11C]PK11195 by PET and Induction of the Peripheral-Type Benzodiazepine Receptor after Transient Focal Ischemia in Rats

Abstract: [ 11 C]PK11195 is used in positron emission tomography (PET) studies for imaging brain inflammation in vivo as it binds to the peripheral-type benzodiazepine receptor (PBR) expressed by reactive glia and macrophages. However, features of the cellular reaction required to induce a positive [ 11 C]PK11195 signal are not well characterized. We performed [ 11 C]PK11195 PET and autoradiography in rats after transient focal cerebral ischemia. We determined [ 3 H]PK11195 binding and PBR expression in brain tissue and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 42 publications
9
106
1
2
Order By: Relevance
“…Since microglia can be activated by elevated cytokine levels indicative of neuroinflammatory processes which are associated with cognitive impairment as well [3,40] animals were also scanned for the uptake of [ 11 C]PK11195. Increased binding of this marker for peripheral benzodiazepine receptors in the brain is regarded as an indication of neuroinflammation [5,29]. However, the PET study revealed no difference in tracer uptake between control animals and animals treated with MTX.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Since microglia can be activated by elevated cytokine levels indicative of neuroinflammatory processes which are associated with cognitive impairment as well [3,40] animals were also scanned for the uptake of [ 11 C]PK11195. Increased binding of this marker for peripheral benzodiazepine receptors in the brain is regarded as an indication of neuroinflammation [5,29]. However, the PET study revealed no difference in tracer uptake between control animals and animals treated with MTX.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, hippocampal sections were immunohistochemically stained with an antibody visualizing ionized calcium binding adapter molecule 1 (IBA-1) which is upregulated in activated microglia [9,17]. Next to this immunohistochemical approach a ligand for peripheral benzodiazepine receptors, [ 11 C]PK11195 (1-(2-chlorophenyl)-N-methyl-N-(1-methylpropyl)-3-isoquinoline carboxamide) was also administered and used as a tracer for PET [5,29]. In normal brain tissue binding of PK11195 is minimal, whereas in areas with activated microglia, in vivo binding is significantly increased [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first in vivo MRI studies on tEAE in rats (Morrissey et al, 1996) showed that MRI changes were observed well before the onset of major cellular infiltration and before the onset of clinical signs that made possible to assess quantitatively the breach of the blood brain barrier (BBB) and to distinguish in vivo between two components of the early phase of the lesion -inflammatory infiltrates and vasogenic oedema. Increased binding of several TSPO ligands has been reported after brain injury, including focal (Myers et al, 1991a;Myers et al, 1991b) and global (Stephenson et al, 1995) cerebral ischemia in the rat where heterogeneous level of expression of TSPO in different cells is seen in the core of infarction as early as 4 days after ischemia (Rojas et al, 2007).…”
Section: Autoradiography and Immunochemistry Correlation With The Uprmentioning
confidence: 99%
“…Several radioligands have been developed to image the activation of microglia in experimental models and in various diseases of the CNS [56] . Early studies in ischemia models using infl ammatory cells [57,58] . In permanent ischemia induced by microspheres injection into the MCA of rats, no increase in 3 H-PK 11195-binding was found in the infarct core 7 days after the attack, but the permanent MCA ischemia caused increased tracer-binding in the normoperfused peri-infarct zone, which was co-localized with increased glucose metabolism and accumulated microglia and macrophages.…”
Section: Microglial Activation As An Indicator Of Infl Ammationmentioning
confidence: 99%